-2x-3=4x+2

Simple and best practice solution for -2x-3=4x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-3=4x+2 equation:


Simplifying
-2x + -3 = 4x + 2

Reorder the terms:
-3 + -2x = 4x + 2

Reorder the terms:
-3 + -2x = 2 + 4x

Solving
-3 + -2x = 2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + -2x + -4x = 2 + 4x + -4x

Combine like terms: -2x + -4x = -6x
-3 + -6x = 2 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + -6x = 2 + 0
-3 + -6x = 2

Add '3' to each side of the equation.
-3 + 3 + -6x = 2 + 3

Combine like terms: -3 + 3 = 0
0 + -6x = 2 + 3
-6x = 2 + 3

Combine like terms: 2 + 3 = 5
-6x = 5

Divide each side by '-6'.
x = -0.8333333333

Simplifying
x = -0.8333333333

See similar equations:

| 2x+(3x/4)=11 | | 2X+2X=68 | | myles=lie | | 4(x^2+6)=168 | | 10y^7+35y^6+25y^5= | | 9-5y=37+2y | | 2x^2=-4+6x | | 500=6x^3+5x^2 | | 2x^2=-4+6 | | 10x+8=4x+25 | | 12m+4n-6m+9n= | | Wow=suchCake | | 6x^2+54=108 | | 2(9X)+2(8X)=68 | | roman=lie | | 18(t-6)+3t=7(3t+2)-8 | | X+2x+4=34 | | 11c-4c= | | swag=pie | | 12-1/3u=12 | | y=8(8)+4 | | (w-5)/(w-1)=(w+2)/(w-3)+1 | | 2x-5=12-45 | | 16(3x-4)=4(12x+1) | | y=8(8)+7 | | 0.36=x/x | | 10pr+8p-5sr-4s= | | 1+2(3x-4)=3(5-x)-4 | | 2x^2-15x+7/6x^2-3x | | (275)(38/55)(11/25) | | x^2-2x=(7+x) | | (w-3)(w-7)=0 |

Equations solver categories